The Influence of Perceived Product Innovation on Purchase Intention through the Mediating Variable of Local Brand Pride in Perfume Products - Adilah Al Humaira; Sulhaini (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The growth of Indonesia’s creative industry highlights the importance of understanding how innovation and consumer perceptions shape purchasing behavior toward local products, particularly in the perfume sector. This research focuses on identifying the role of Local Brand Pride in mediating the influence exerted by Perceived Product Innovation on Purchase Intention within Indonesia’s local perfume product segment. This study employs a quantitative causal-associative design, with data collected through structured questionnaires from 150 consumers of local perfume products in Indonesia and analyzed using SmartPLS 4. The results indicate that Perceived Product Innovation has a significant positive effect on Purchase Intention and Local Brand Pride, while Local Brand Pride significantly influences Purchase Intention and acts as a mediating variable. From practical and policy perspectives, these findings suggest that innovation-driven product development can foster pride in local brands and enhance consumers’ willingness to purchase. Future research is encouraged to explore additional psychological or cultural variables and to extend the analysis to other creative industry sectors.